Effect of a Four-week Core Stability Training Program on the Kinetic Parameters in Athletes With Functional Ankle Instability During Single-leg Drop Landing - Narges Pirmohammadi; Elham Shirzad; Hooman Minounejad (Sport Sciences and Health Research)
Introduction: This study aimed to investigate the effect of a 4-week core stability training program on landing kinetic parameters in athletes with functional ankle instability during a single-leg drop landing exercise. Methods: This study used a pre-post quasi-experimental design and was conducted in the biomechanics laboratory. A total number of 24 athletes with functional ankle instability participated in two experimental (n=12) and control (n=12) groups. The experimental group performed core stability training for 4 weeks. The kinetic variables (maximum vertical Ground-Reaction Force [GRF], maximum shear GRF, and time to peak vertical GRF) were measured with force plate at the frequency of 400 Hz, in the pre-test and post-test. The obtained data were compared using Analysis of Covariance (ANCOVA) and multivariate analysis of covariance MANCOVA in SPSS V. 18. Results: In the experimental group, all variables significantly differ between the pre-test and post-test. Also, the ANCOVA and MANCOVA indicated significant differences between the experimental and control groups in all variables. Conclusion: The results indicated that the core stability training improved the kinetic parameters of landing in people with functional ankle instability; thus, it can reduce the re-injury risk of the ankle.